The Performance of Islamic Religious Counselors in Fostering Sakinah Families for Converts in Deli Serdang Regency from the Perspective of Maqashid Al-Syariah - Ahmad Kosasih Daulay; Dhiauddin Tanjung; Ramadhan Syahmedi Siregar (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to examine the performance of Islamic Religious Counselors in fostering a harmonious family for converts in Deli Serdang Regency from the perspective of maqashid al-syariah. The method in this study uses a descriptive qualitative approach; data is collected through interviews, observations, and documentation of religious counselors, religious affairs offices, and converts who are being fostered. The results of the study show that religious instructors not only carry out their role as preachers, but also as managers of coaching programs that include planning, organizing, mobilizing, and supervising functions. The coaching process is carried out formally and informally through lectures, interpersonal sharing, digital media, and home visits, with materials that emphasize the importance of family resilience, religious understanding, and moral values. All these efforts reflect the implementation of the values ??of maqashid al-syariah, especially in maintaining religion (hifz al-din), soul (hifz al-nafs), reason (hifz al-‘aql), descendants (hifz al-nasl), and property (hifz al-mal), so that development is not only ceremonial but becomes a process of spiritual and social transformation towards a peaceful family based on Islamic law.